A Snapshot of Teachers’ Teaching Experience through the Lens of Gagné’s Nine Instruction Events - Audi Yundayani; Fiki Alghadari; Arini Noor Izzati (Universitas Pendidikan Ganesha, 2025)
Gagné Nine Events of Instruction framework enhances cognitive processing and student engagement. Thus, teachers are very important to the teaching process because they assess students’ requirements, create lesson plans, employ teaching methods, and evaluate the effectiveness of their teaching. There is a need for further research on how teachers apply Gagné’s Nine Events of Instruction in their classrooms, as student-centered learning becomes increasingly popular. This is a decriptive qualitative research. There are fifty-three participants taking part in this qualitative study, three of whom are interviewees. Data collection utilizes questionnaires and semi-structured interviews, with analysis conducted through thematic analysis. The results reveal the integration of Gagné’s instructional events during the pre-teaching phase, which includes capturing students’ attention, outlining objectives, and activating prior knowledge; during the teaching phase, which encompasses content presentation, guidance for learning, and performance elicitation (practice); and the post-teaching phase, which involves providing feedback, assessing performance, and facilitating retention and transfer, albeit with some inconsistencies in implementation. Teachers need to continue learning and recognize the importance of these ideas in achieving learning goals. To improve education, policymakers should invest significant effort in enhancing teacher effectiveness.